Enhancing Eleventh Graders’ Reading Skills through Content-Based Instruction Using Multimodal Texts: A Mixed-Methods Study - Istikomah; Achmad Yudi Wahyudin (Universitas Islam Negeri Palopo, 2025)
In this study, eleventh-grade students at SMAN 14 Bandar Lampung's reading comprehension skills are improved through the use of Quiz.com and multimodal texts to promote Content-Based Instruction (CBI). Utilizing a mixed-methods methodology, the research integrated both qualitative and quantitative techniques to present a thorough analysis of the intervention. Thirty-one pupils answered a 15-item Likert-scale survey to gauge their impressions, motivation, and engagement, and they took part in a pre- and post-test to gauge their reading comprehension. In the quantitative findings, the mean score increased from 83.41 in the pre-test to 95.74 in the post-test, indicating a considerable improvement. The paired samples t-test verified that the change was statistically significant (p <.05). Additionally, the standard deviation dropped from 16.38 to 4.97, indicating that students' performance stabilized following the intervention. All five components of reading comprehension—main concept identification, supporting detail recognition, contextual vocabulary knowledge, inference-making, and text structure analysis—showed growth in the students. These conclusions were corroborated by the questionnaire results, which showed high internal consistency with a Cronbach's Alpha of.936. Responses were largely positive, according to content analysis, with mean ratings ranging from 3.81 to 4.58. Quiz.com's engaging, entertaining, and inspiring aspects were especially appreciated by students, and multimodal texts were acknowledged for giving reading greater significance and relevance to everyday situations. Nevertheless, several students pointed out that multimodal texts did not totally eliminate monotony, indicating the necessity for a variety of teaching methods. Overall, the results show that understanding, motivation, and confidence in EFL classes may be successfully increased by including CBI, multimodal resources, and digital technologies.